(3eUfa GHf CHj TjHgs - (3CHh HcQ YHO Gddg Hf eMeO Hf CHj TjHI GdYHSj, GHf CHj TjHI,J (B235 (3g` s
(3ChdgG (B:s
(3ef QaV Cf jLeY GdQLd Hjf GeQCI QLd hGHfJI ef ZjQgG s
(3BNQgG (B:s
(3hjfJgi (B: (3HfgGjI cJGH GdCbVjI s
(3LRA efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B117s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B104 s
(3eUOQ GbJfGA GdCUd (B:s
(3YehejI (B(1189) s
Keywords: (3GdMOjK h GdeUWdMs